PENGARUH PARTIAL REPLACEMENT SEMEN PORTLAND DENGAN BENTONITE TERHADAP KUAT TEKAN BETON BERDASARKAN VARIASI UMUR - Encik Junaidi Aprizal, Pusoko Prapto (Universitas Negeri Yogyakarta, 2015)
ABSTRACTThis study aims to get the maximum compressive strength with high quality in determining theeffect of partial replacement of cement with bentonite to the compressive strength of concrete.This study was conducted by testing the chemical composition of the bentonite by using themethod of Atomic Absorption Spectrometry (AAS) and Gravimetry that refers to the ASTM 618-03. For testing the compressive strength of concrete it was used the age variation to assess thecompressive strength of concrete using 10% of bentonite as the partial replacement for cement.There were 18 samples consisting of three cylindrical concrete samples in each age variation(the diameter was 150 mm and the height was 300 mm) and the testing was conducted at theage of 3, 7, 14, 21, 28 and 56 days. The results showed that the test of bentonite chemicalcomposition in the Chemistry Analytical Laboratory of Gadjahmada University met therequirements of pozolan chemical. The highest compressive strength at the age of 56 days andat 28 days the lowest compressive strength were 49.454 MPa and 37.119 MPa respectively.The percentage of the optimum increase of concrete obtained at the age of 28 days to 56 dayswas 33.23%. Moreover the addition of bentonite gives the effect to the workability so that thevalue of the slump was lower than the that in the planning.Keywords: Bentonite, Compressive strength, Slump